Depresi Postpartum: Studi Retrospektif dengan Menganalisis Dukungan Suami Saat Persalinan - Gayatri, Ni Luh Putu; Parwati, Ni Wayan Manik; Dwiyanti, Ni Kadek Neza; Haryati, Ni Putu Sri (STIKES Karya Husada Kediri, 2023)
The postpartum period is a vulnerable period which can cause psychological disorders. One of them is postpartum depression. Generally, postpartum depression happened 13%. One of the social supports which influence during labor is husband support. However, not all of husband can give these supports. The objective is To determine the correlation between husband support during labor and postpartum depression incidence on postpartum mother. This study employed analytical correlation design. It was analyzed by using Spearman Correlation Test to determine the correlation with retrospective approach by using questionnaire. The data were collected by using total sampling technique in April- May 2023. There were 54 postpartum mothers recruited as the samples starting day 7-42 days in the working area of Public Health Center I South Denpasar. The result of spearman correlation test showed there was no correlation between husband support during labor and postpartum depression (p-value = 0,137 > 0,05). It showed 11% of mothers had risk of postpartum depression caused by less of husband support during labor. Depression incidence is not only influenced by internal factors but also external factor such as husband support. Husband support is not only needed during labor, but also it can be done everyday during postpartum. It is very important to reduce postpartum depression. Keywords: Experience, Postpartum Mother, Husband Support, Postpartum Depression